The Capability to 'Have It All: Exploring how Socioeconomic Conditions Affect Married Women Direct Sellers' Lives - Nurfadilah, Adella (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
The 'have it all' ideology has proven challenging; thus, many married women turn to direct selling. While offering easiness, recent studies highlight its potential exploitation, particularly among low-income individuals. This study addresses the scarcity of qualitative research on married women in Indonesia's beauty industry who engage in direct selling, examining how socioeconomic conditions impact their lives. Through snowball sampling and in-depth interviews among 16 married women direct sellers, the findings indicated that socioeconomic status enhances their ability to balance multiple roles. However, success is not assured, regardless of initial conditions. These findings are pivotal for policymakers and practitioners seeking to establish a fairer, more empowering environment for women.